The Study of Musical Structure and Form: Kirk Franklin's Stylistic Approach in Arrangement of the Song 'Pengharapanku' - Fiqri Agam Trahnata; IGN Wiryawan Budhiana; Tanesya Hotris Samosir (Tehilla: Jurnal Seni Budaya dan Musik Gereja, 2025)
This study examines the arrangement process of the hymn Pengharapanku by adapting Kirk Franklin’s gospel style. The research aims to explore the integration of modern gospel musical elements into the Indonesian church music repertoire without diminishing its spiritual essence. The method combines musical analysis and arrangement practice, encompassing both conceptual and implementation stages, with emphasis on harmony, rhythm, dynamics, and vocal techniques. The findings reveal that the use of extended chords, altered chords, chord inversions, modulation, and syncopation enriches harmonic color and expands musical expression. In addition, vocal techniques such as melisma and riffs and runs strengthen the distinct gospel character inspired by Kirk Franklin’s style. The study highlights the importance of contextual approaches in the development of liturgical music, particularly in diversifying church repertoires that remain relevant to contemporary congregational needs. Future research is recommended to extend the scope by comparing gospel styles of other composers and exploring congregational responses to gospel-inspired arrangements in worship practices, thereby contributing to both academic discourse and the practical advancement of church music in Indonesia.